In vivo genotoxicity assessment of nerolidol - Piculo, Fernanda [UNESP]; Macedo, Ceci Guiraldeli [UNESP]; de Andrade, Sergio Faloni; Maistro, Edson Luis [UNESP] (Wiley-Blackwell, 2011)
Nerolidol is a sesquiterpenoid component of essential oil used as a flavor and aroma enhancer. It has also been studied as a topical skin penetration enhancer, and has inhibitory activities against S. aureus and E. coli, among other activities. The objective of this study was to evaluate the ability of a single nerolidol treatment to induce DNA damage in peripheral blood and liver cells of mice and micronuclei in polychromatic erythrocytes of bone marrow cells of the same animals. In the dose range-finding assays, the maximum tolerated dose was higher than 2000 mg kg(-1). The doses used in the experiments were 250, 500 and 2000 mg kg(-1), administered by gavage in a single dose. Peripheral blood cells were collected 4 and 24 h after the treatments and liver cells 24 h after. At least 100 nucleoids per cell type/animal were analyzed to determine the DNA damage scores and 2000 PCEs per animal for micronuclei in PCEs. The positive control was N-nitroso-N-ethylurea 50 mg kg(-1). Cytotoxicity was assessed by scoring 200 consecutive total polychromatic (PCE) and normochromatic (NCE) erythrocytes (PCE: NCE ratio). The results showed that nerolidol induced weak levels of dose-related DNA damage in both types of cells analyzed, and enhanced the average number of micronucleated cells in the two high doses tested. The PCE: NCE ratio showed no cytotoxicity for the three doses of the compound. The data obtained support the view that nerolidol induces clastogenicity and very weak genotoxicity in the mouse cells tested. Copyright (C) 2010 John Wiley & Sons, Ltd.
Keywords: nerolidol; micronucleus test; essential oil; comet assay; clastogenicity; Baccharis dracunculifolia